2021
DOI: 10.1002/ece3.7316
|View full text |Cite
|
Sign up to set email alerts
|

Small cats in big trouble? Diet, activity, and habitat use of jungle cats and leopard cats in threatened dry deciduous forests, Cambodia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 69 publications
(95 reference statements)
0
15
0
Order By: Relevance
“…In addition to these studies, consumption of deer by hunting or scavenging by leopard cats has been reported, e.g., Tragulus javanicus (lesser mouse deer) in Thailand [ 9 ] and Muntiacus spp. (muntjac) in Cambodia [ 15 ] and Laos [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these studies, consumption of deer by hunting or scavenging by leopard cats has been reported, e.g., Tragulus javanicus (lesser mouse deer) in Thailand [ 9 ] and Muntiacus spp. (muntjac) in Cambodia [ 15 ] and Laos [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…sibirica was reported to be detected from a feces of leopard cat in Korea [ 17 ]. Although it is unclear whether it is predation or scavenging, it has been reported that carnivorous animals were detected in the feces of leopard cats, e.g., Nyctereutes procyonoides (raccoon dog) in the Russian Far East [ 11 ], Urva auropunctata (small Indian mongoose) and Herpestes edwardsii (grey mongoose) in Pakistan [ 13 ], and civet in Cambodia [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that the dense wide columns of processional termites are relatively efficient for jackals to lick up and consume in large quantities, thereby providing an important source of protein for jackals during the dry season in DDF, especially when larger prey items become less available. Interestingly, concurrent dietary studies in SWS using DNA-confirmed scats showed that leopards, dholes, jungle cats, and leopard cats did not consume processional termites beyond negligible amounts ( Rostro-García et al 2018 , In press ; Kamler et al 2020d ), indicating jackals were the only canid or felid species to take advantage of this food resource during the dry season.…”
Section: Discussionmentioning
confidence: 99%
“…We took a random sample of 10 putative jackal scats collected from shrubs and tufts of grass, and sent them to the Sackler Institute for Comparative Genomics, American Museum of Natural History (New York), who confirmed that the scats were from jackals based on mitochondrial DNA analysis as described by Caragiulo et al (2014) . Concurrent diet studies used DNA analysis to confirm that other carnivore scats collected in SWS belonged to leopards ( n = 73 scats— Rostro-García et al 2018 ), dholes ( n = 165— Kamler et al 2020d ), jungle cats ( n = 16) and leopard cats ( n = 130— Rostro-García et al In press ), none of which were found to defecate on small shrubs or tufts of grass. We therefore were confident that all the carnivore scats collected from small shrubs and tufts of grass along trails and dirt tracks were from jackals.…”
Section: Methodsmentioning
confidence: 99%